2021
DOI: 10.1136/gpsych-2020-100343
|View full text |Cite
|
Sign up to set email alerts
|

Case series associated with COVID-19 pandemic in causing psychiatric morbidity

Abstract: The COVID-19 has emerged as a public health emergency across the globe. Countries all over the world have been forced to enforce nationwide lockdowns to curb the transmission of this illness, affecting millions of people. The disorder and the lockdowns enforced have resulted in a complex set of psychosocial stressors in the lives of people, affecting their resilience and causing psychological stress and mental health issues. In this case series, we aim to highlight the role of such psychosocial stressors in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…This raises concern that stress-related reactions to the infection are an additional confounding variable. The COVID-19 pandemic places children and adolescents under significant social and family stress [ 5 ]. In the second case, there was a complex family dynamic, and the patient’s parents held opposing views regarding the etiology of his symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This raises concern that stress-related reactions to the infection are an additional confounding variable. The COVID-19 pandemic places children and adolescents under significant social and family stress [ 5 ]. In the second case, there was a complex family dynamic, and the patient’s parents held opposing views regarding the etiology of his symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The few adolescent cases of psychosis that have been reported were associated with high levels of psychosocial stress [ 5 ]. It is well known that the COVID-19 pandemic caused significant stress to adults and children worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…8. Mahapatra et al, [23] reported on 3 cases. Case 1 was a 48-year-old male hospitalized for COVID-19 and whose mother died simultaneously due to COVID-19.…”
mentioning
confidence: 99%